Response of growth and development of butternut squash (Cucurbita moschata) to the combination of bioslurry and NPK fertilization. Issue 1 (October 2020) - Dermawan, R; Kaimuddin,; Dungga, N E; Sjahril, R; Mollah, A; Yuniarti, N S
Abstract: This study aims to study the effect of bioslurry and NPK fertilizers and to determine the best dosage of bioslurry and NPK fertilizer on the growth and development of butternut squash. The study was conducted from December 2018 to 21 March 2019 in Purnakarya Village, Tanralili District, Maros Regency, South Sulawesi. The study was set as a trial using a split plot design. The main plot was three bioslurry concentrations namely control, 100, and 200 mL L −1 bioslurry. The subplot was the application of NPK fertilizer types consisted of four levels, namely NPK Pak Tani (16-16-16), NPK Gold (16-10-18), NPK RG05 (15-10-30), and NPK Booster (12-6-22-3). The results of the experiment show that there was a significant interaction between bioslurry and NPK types on the stem diameter of butternut squash plants (bioslurry 100 mL L −1 and NPK Pak Tani). The bioslurry treatment showed a significant effect on fruit weight by the application of bioslurry 200 mL L −1 (978.42 g). NPK treatment significantly affected fruit length with use of NPK Pak Tani that resulted in the longest fruit (24.58 cm).